Urachal mucinous cystadenoma: An exceptional entity - Chaabouni, Ahmed (Urol Case Rep, 2021)
Urachal villous adenoma is a rare entity. We aimed to share a case of a giant villous adenoma that was treated surgically. Surgery was uneventful and flow up was normal.